2019
DOI: 10.3390/buildings9050123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Natural Ventilation on the Thermal and Energy Performance of Buildings in a Mediterranean Climate

Abstract: Natural ventilation plays an important role on the thermal and energy performance of a building. The present study aims to analyze the natural ventilation conditions of a dwelling in a Mediterranean climate and their impacts on the thermal and energy performance using an advanced building energy simulation tool. Several multi-zone simulations were carried out. In the summer, the simulations were performed under free-floating conditions, whereas in the winter they were carried out under controlled temperature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Among the most important parameters of investigating the thermal and the energy performance of buildings in the Mediterranean climate are the natural ventilation conditions using advanced building energy simulation tools [45]. In this study, several multi-zone simulations were carried out and it was concluded that the stack effect plays an important role in the ventilation and that it is commonly outperforms the wind effect.…”
Section: Exploration Of Other In-house Interventionsmentioning
confidence: 98%
“…Among the most important parameters of investigating the thermal and the energy performance of buildings in the Mediterranean climate are the natural ventilation conditions using advanced building energy simulation tools [45]. In this study, several multi-zone simulations were carried out and it was concluded that the stack effect plays an important role in the ventilation and that it is commonly outperforms the wind effect.…”
Section: Exploration Of Other In-house Interventionsmentioning
confidence: 98%
“…More importantly, the target discomfort hours were met in bedroom 1, with 54.40% reduction in discomfort hours from the reference model, as a result of the modification of operation schedule and the specific reduction of openings in bedroom 1. Incoming air is detrimental to thermal comfort particularly in the winter, while ventilation can be used to cool the building in other seasons (Moret Rodrigues et al, 2019). It is evident from the results that rather than ventilating, insulating the residence in winter 2021/2/29…”
Section: Figmentioning
confidence: 99%
“…The benefits of natural ventilation have led to its increased use in a wide range of settings including residential and commercial. However, there are several challenges when using natural ventilation for indoor thermal comfort such as difficulty to predict uncertainties arising due to variable meteorological conditions and inability to control occupant behaviour on windows operation (Moret Rodrigues et al, 2019). The effective application of natural ventilation for thermal comfort is also reliant on the season and climate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to experimental measurement complexity, some parameters were adopted according to References [20,24], such as: minimum stomatal resistance of 180 s/m, leaf emissivity/reflectivity of 0.95/0.25, and thermal/solar/visible absorptance of 0.9/0.8/0.8. Lisbon is classified as a Csa Mediterranean climate according to the Köppen-Geiger classification due to its hot and dry summers and mild to cool wet winters, high solar radiation, and uneven rainfall patterns [21][22][23]. As fall and spring do not present substantial energy needs and indoor thermal discomfort conditions, the thermal performance of the green roof was monitored separately during two representative periods: a heating season from 21-30 January and cooling season from 5-11 July 2013.…”
Section: Case Study: Experimental and Numerical Evaluationmentioning
confidence: 99%